Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1476-5381.1993.tb13875.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the phospholipase C pathway by ATP is mediated exclusively through nucleotide type P2‐purinoceptors in C2C12 myotubes

Abstract: 1 The presence of a nucleotide receptor and a discrete ATP-sensitive receptor on C2C12 myotubes has been shown by electrophysiological experiments. In this study, the ATP-sensitive receptors of C2C12 myotubes were further characterized by measuring the formation of inositol(1,4,5)trisphosphate (Ins(1,4,5)P3) and internal Ca2+. 2 The nucleotides ATP and UTP caused a concentration-dependent increase in Ins(1,4,5)P3 content with comparable time courses (EC5o: ATP 33 ± 2 JAM, UTP 80 ± 4 jaM). ADP was less effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…At least three different P2-purinoceptors are present in mouse C2C12 myotubes: a P2u-purinoceptor coupled to phospholipase C (Hemming et al, 1992;1993a) and two unclassified P2-purinoceptors activating Na+-influx (Henning et al, 1992) and the formation of cyclic AMP (Henning et al, 1993b), respectively. Experiments using different purinoceptor agonists have shown that the ATP-evoked increase in cytoplasmic Ca2" in these cells is exclusively mediated by the nucleotide type P2U-purinoceptor (Henning et al, 1993a).…”
Section: P2-purinoceptor-mediated Ca2+ Responsementioning
confidence: 99%
See 4 more Smart Citations
“…At least three different P2-purinoceptors are present in mouse C2C12 myotubes: a P2u-purinoceptor coupled to phospholipase C (Hemming et al, 1992;1993a) and two unclassified P2-purinoceptors activating Na+-influx (Henning et al, 1992) and the formation of cyclic AMP (Henning et al, 1993b), respectively. Experiments using different purinoceptor agonists have shown that the ATP-evoked increase in cytoplasmic Ca2" in these cells is exclusively mediated by the nucleotide type P2U-purinoceptor (Henning et al, 1993a).…”
Section: P2-purinoceptor-mediated Ca2+ Responsementioning
confidence: 99%
“…Ins(1,4,5)P3 measurement Ins(1,4,5)P3 contents of the myotubes was assessed by mass measurement with a radioligand binding assay as described by Henning et al (1993a). Before the experiment, the cells were washed two times in the standard buffer and a final wash was performed with the Ca2"-free buffer.…”
Section: Intracellular Ca-`measurementmentioning
confidence: 99%
See 3 more Smart Citations